Pengaruh Terpaan dan Kredibilitas Media Online Akun Instagram @Naikmotor Terhadap Pemenuhan Kebutuhan Followers - Gumay, Muhamad; Banowo, Emilianshah (Jurnal Bisnis dan Komunikasi Digital, 2025)
This study aims to analyze the influence of media exposure and credibility on the information needs of followers of the Instagram account @naikmotor, which focuses on the automotive sector. The quantitative method was used, with data collected through questionnaires distributed to 400 respondents using a four-point Likert scale ranging from "strongly agree" to "strongly disagree." The results showed a significant influence of media exposure (X1) and credibility (X2) conveyed by the @naikmotor account on the fulfillment of followers' information needs (Y), and the other is influenced by other factors outside this study. The higher the media exposure and credibility provided, the greater the fulfillment of followers' information needs. The normality test, conducted using the One-Sample Kolmogorov-Smirnov Test with the Monte-Carlo method, showed that the data met the assumptions for further statistical analysis or is said to be normally distributed. The F-test results indicated a significant relationship between the independent and dependent variables, with a highly significant F-table value. Additionally, this study highlights the importance of trust in writing news, emphasizing the need for credible sources and the dissemination of accurate information by the @naikmotor account. These findings suggest that increasing the credibility of media content can enhance followers' information satisfaction, resulting in a more informed audience in the automotive industry. This research provides insights for media practitioners and marketers to engage more effectively with audiences on social media.